Retrospective analysis of attitudes to ageing in the Economist: apocalyptic demography for opinion formers. - O'Neill, Desmond (My University, 2009)
Objective To investigate the description of older people and ageing in a major weekly newspaper, influential in political and financial circles, to see whether it reflected ageing in a balanced manner, and to what extent it indulged in apocalyptic demography?the portrayal of population ageing as a financial burden rather than a scientific advance. Design Electronic search of the digital archive of the Economist of articles published between January 1997 and April 2008. Main outcomes measures Categorisation of articles as portraying population ageing as a burden or a benefit or with a balanced view. Results Of 6306 identified articles, 262 were relevant. Most featured pensions, demography, and politics. Of these 262, 64% portrayed population ageing as a burden and 12% as a benefit; 24% had a balanced view. Most articles therefore showed a predominantly ageist view of older people as a burden on society, often portraying them as frail non-contributors. Recurrent themes included pension and demographic "time bombs" and future unsustainable costs of health care for older people. Conclusion This negative view of older people might be influential in shaping the attitudes of readers, who include opinion formers in political and economic circles. Gerontologists (including geriatricians) need to engage with influential media, as well as helping to promote a professional development of journalists that is informed and knowledgeable about the negative impact of ageism on the wellbeing of older people.
PUBLISHED
Christmas Edition
Keywords: Clinical Medicine; International Integration